We hunt the flame - Faizal, Hafsah (Macmillan Children's Books, 2021)
People lived because she killed. People died because he lived. Zafira is the Hunter. Force to disguise herself as a man, she risks everything to provide for her people. Nasir is the Prince of Death. A feared assassin who is forever bound to the command of his father, the sultan. Both are legends in their kingdom - but neither wants to be. And when Zafira embarks on a dangerous quest to return magic to their suffering land, Nasir is sent on a similar mission. But as their journey unfolds, an ancient evil begins to stir...